The Use of Todaii German Application as a Self-Learning Media on Listening Skill of German Language Education Students at State University of Malang - Mamik Utami; Herri Akhmad Bukhori (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2025)
This study aims to describe the use of Todaii German application as a self-learning media on listening skill of German Language Education students at State University of Malang. This type of research is descriptive qualitative research involving 47 students form Offering A, B, and C Class of 2023 German Language Education Study Program, State University of Malang as research subjects. The research data was obtained through observation and questionnaire sheets. The observation data was used to describe the process of applying Todaii German, while the questionnaire data was used to determine student responses related to the use of the Todaii German application as a self-learning media on German listening skill. The observation results stated that students were able to understand and to follow the instructions explained by the researcher and easily to use the Todaii German application. The result of the student questionnaire gave a positive response to this application, but there were obstacles found, namely internet connection problems, audio that sounded too stiff, and limited premium access problems. In general, the results showed that the Todaii German application can be used as a learning media in helping students practice listening skill independently.